Cuidado profesional de enfermería en mujeres con ruptura prematura de membranas - Pazmiño Aranda, Jefferson Edgar (2018)
Nursing care for pregnant women with premature rupture of membranes plays an important role, since this complication represents a risk for maternal-fetal well-being. At present, this pathology is a serious problem worldwide, becoming a cause of maternal morbidity and mortality. Premature rupture of membranes is defined as the loss of integrity of the fetal membranes before the onset of labor and can occur spontaneously from week 20 of gestation. This bibliographic review aims to determine the professional care of Nursing in women with premature rupture of membranes; for this purpose, the search and revision of several updated documents related to the subject was carried out through databases such as: Scopus, MedLine, Bireme, Pubmed. The results obtained were the criterion of 17 authors who describe the professional care needs in relation to 10 problems presented in RPM.